Diagnostic criteria for acute‐onset type 1 diabetes mellitus (2012): Report of the Committee of Japan Diabetes Society on the Research of Fulminant and Acute‐onset Type 1 Diabetes Mellitus. Issue 1 (13th August 2013) - Kawasaki, Eiji; Maruyama, Taro; Imagawa, Akihisa; Awata, Takuya; Ikegami, Hiroshi; Uchigata, Yasuko; Osawa, Haruhiko; Kawabata, Yumiko; Kobayashi, Tetsuro; Shimada, Akira; Shimizu, Ikki; Takahashi, Kazuma; et al.
Abstract Type 1 diabetes is a disease characterized by destruction of pancreatic β‐cells, which leads to absolute deficiency of insulin secretion. Depending on the manner of onset and progression, it is classified as fulminant, acute‐onset or slowly progressive type 1 diabetes. Here, we propose the diagnostic criteria for acute‐onset type 1 diabetes mellitus. Among the patients who develop ketosis or diabetic ketoacidosis within 3 months after the onset of hyperglycemic symptoms and require insulin treatment continuously after the diagnosis of diabetes, those with anti‐islet autoantibodies are diagnosed with 'acute‐onset type 1 diabetes mellitus (autoimmune)'. In contrast, those whose endogenous insulin secretion is exhausted (fasting serum C‐peptide immunoreactivity <0.6 ng/mL) without verifiable anti‐islet autoantibodies are diagnosed simply with 'acute‐onset type 1 diabetes mellitus'. Patients should be reevaluated after certain periods in case their statuses of anti‐islet autoantibodies and/or endogenous insulin secretory capacity are unknown.